2023
DOI: 10.3390/ctn7030016
|View full text |Cite
|
Sign up to set email alerts
|

A Turkish Validity and Reliability Study of the Swiss Narcolepsy Scale

Abstract: Background: The clinical evaluation of a patient complaining of excessive daytime sleepiness is of crucial importance for the diagnosis of narcolepsy. The Swiss Narcolepsy Scale (SNS) was developed in 2004 as a screening tool for patients with narcolepsy and shown in three different studies to have a high sensitivity and specificity for narcolepsy type 1 (NT1). The aim of this study was to assess the validity and reliability of the Turkish version of SNS (SNS-TR). Patients and Methods: Twenty-one healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Similar results were demonstrated by Bargiotas et al [16], with relatively low sensitivity (56%) as well as specificity (68%). Demir et al [17] showed, however, that the ESS scores were significantly higher (p = 0.033) in patients with narcolepsy (NT1 or NT2) compared to IH. There were no significant differences in the ESS scores between NT1 and NT2.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar results were demonstrated by Bargiotas et al [16], with relatively low sensitivity (56%) as well as specificity (68%). Demir et al [17] showed, however, that the ESS scores were significantly higher (p = 0.033) in patients with narcolepsy (NT1 or NT2) compared to IH. There were no significant differences in the ESS scores between NT1 and NT2.…”
Section: Discussionmentioning
confidence: 95%
“…[1] never, [2] rarely (less than once a month), [3] sometimes (1-3 times a month), [4] often (1-2 times a week), and [5] almost always Q5 How often have you experienced sagging of the jaw during emotions like laughing, happiness, or anger? [1] never, [2] rarely (less than once a month), [3] sometimes (1-3 times a month), [4] often (1-2 times a week), and [5] Demir et al [17] have recently assessed the validity and reliability of the Turkish version of the SNS (SNS-TR). The overall sensitivity and specificity of the SNS-TR in diagnosing NT1 are 90.5% and 100%, respectively.…”
Section: Table 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation